Peran Kuliner Pasar Lama Dalam Meningkatkan Citra Destinasi Pariwisata Kota Tangerang - Roozana Maria Ritonga (Jurnal Sains Terapan Pariwisata, 2020)
Culinary has an important role in the tourism industry because most of the expenditure of tourists is for food and drinks. In 2017 culinary alone reaches a percentage of around 30-40 percent spent by tourists in Indonesia. Tourism destinations that have unique culinary can motivate tourists to travel to Pasar Lama area in Tangerang City. Tangerang City is one of the tourism destinations in Banten Province and ranks the third largest in the Jabodetabek area after Jakarta. This strategic location makes Tangerang City have opportunities for the development of various fields of activity, one of which is the tourism sector. Tangerang City needs to have a good image to be different in the minds of tourists. To improve the image of a destination we can use culinary in the city of Tangerang which was inaugurated in 2012 under the name Pasar Lama Culinary Area. This area is formed from history which was once the oldest trade center in the city of Tangerang and cultural heritage because this area is formed with cultural acculturation. This research method uses descriptive qualitative. Data sources obtained by interview, observation, and documentation. Data analysis uses four stages, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results, the role of culinary is sufficient to contribute in upgrading the image of Tangerang City with the supporting and inhibiting factors in improving the image of the tourism destination of Tangerang. Supporting factors include: the taste of food, food ingredients, price setting, and casual atmosphere while the inhibiting factors are: human aspects, cleanliness, placement of culinary carts that are less organized, buskers and less extensive pedestrian paths.